Digitalization of Micro, Small and Medium Enterprises in Nagari Muaro Pingai, Junjung Sirih District, Solok Regency, West Sumatra - Elsa Eka Putri; Masyhuri Hamidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
This program aims to introduce the benefits of science and technology to Micro, Small, and Medium Enterprises (MSMEs) in Nagari Muaro Pingai due to the limited market share and need for more awareness of products produced by these MSMEs. Through this digitalization work program, the community service team from Universitas Andalas assisted five MSME entrepreneurs by strengthening their business branding, providing financial assistance, and digital promotion. The methods employed include direct data collection, interview surveys, and providing training directly to the community. The financial assistance included mobile phones to help them digitize their businesses. The outcomes of those MSME's digitalization work programs included business logos, promotional brochures, and business location registration on the Google Maps platform. The community engagement activities further expanded market reach, increased income, and simplified transaction processes for MSME entrepreneurs in Nagari Muaro Pingai.